Chromosomal Diversification in Ancistrus Species (Siluriformes: Loricariidae) Inferred From Repetitive Sequence Analysis - Santos da Silva, Kevin; Glugoski, Larissa; Vicari, Marcelo Ricardo; de Souza, Augusto César Paes; Noronha, Renata Coelho Rodrigues; Pieczarka, Julio Cesar; Nagamachi, Cleusa Yoshiko (Frontiers in Genetics, 2022)
The Ancistrus genus has extensive chromosomal diversity among species, including heteromorphic sex chromosomes occurrence. Studies have been shown that this chromosomal diversity may still be underestimated. Repetitive sequences represent a large part of eukaryotic genomes, associated with mechanisms of karyotypic diversification, including sex chromosomes evolution. This study analyzed the karyotype diversification of two Ancistrus species (Ancistrus sp. 1 and Ancistrus sp. 2) from the Amazon region by classical and molecular chromosomal markers. Conventional chromosome bands and fluorescence in situ hybridization using probes 18S and 5S rDNA, besides (CA)n, (CG)n, (GA)n, (CAC)n, (CAG)n, (CAT)n, (GAA)n, (GAC)n, (TAA)n, and (TTAGGG)n in tandem repeats were determined on the karyotypes. Ancistrus sp. 1 and Ancistrus sp. 2 presented karyotypes with 2n = 38 (20m+14sm+4st, XX/XY) and 2n = 34 (20m+14sm, without heteromorphic sex chromosomes), respectively. Robertsonian rearrangements can explain the diploid number difference. C-bands occurred in pericentromeric regions in some chromosomes, and a single 18S rDNA locus occurred in both species. The 5S rDNA showed variation in the number of loci between species karyotypes, suggesting the occurrence of unstable sites and rearrangements associated with these sequences in Ancistrus. The microsatellite mapping evidenced distinct patterns of organization between the two analyzed species, occurring mainly in the sex chromosomes in Ancistrus sp. 1, and in the centromeric and pericentromeric regions of chromosomes m/sm in Ancistrus sp. 2. These data show the extensive chromosomal diversity of repetitive sequences in Ancistrus, which were involved in Robertsonian rearrangements and sex chromosomes differentiation.